An Initial Model for Generative Design Research: Bringing together Generative Focus Group (GFG) and Experience Reflection Modelling (ERM) - Bakirlioğlu, Yekta; Oğur, Dilruba; Doğan, Çağla; Turhan, Senem (Design and Technology Education: An International Journal, 2016)
Understanding people’s experiences and the context of use of a product at the earliest stages of the design process has in the last decade become an important aspect of both the design profession and design education. Generative design research helps designers understand user experiences, while also throwing light on their current needs, preferences and future expectations. In this paper, two complementary methods, namely the Generative Focus Group (GFG) approach and Experience Reflection Modelling (ERM), will be presented through a research case focusing on the development of sustainable design considerations in the areas of effective use of resources, and product maintenance and repair. The first method makes use of generative tools (i.e. diaries and timelines) to gain feedback from a group of experienced users. It facilitates group discussions and enables engaging user participation to develop potential design directions. In contrast, the second method utilizes a special toolkit of abstract two- and three-dimensional product parts to reveal the needs, preferences, and expectations of the individual in a more in-depth manner, with the intention being to further explore the insights and design directions that emerged during the application of the first method. This paper proposes an initial model that brings together these two methods, incorporating generative tools and techniques that are adaptable, participatory and engaging, and discusses their implications for design education.